Botswana : Technical Assistance Report-Government Finance Statistics. (IMF Staff Country Reports; Country Report ;, 2018)
A Government Finance Statistics (GFS) technical assistance (TA) mission visited Gaborone, Botswana, during October 9-20, 2017 to support the Botswana Ministry of Finance and Economic Development (MFED) in improving compilation and dissemination of fiscal statistics. The mission provided assistance with: (i) disaggregation of expense transactions in the statement of operation in accordance with the Government Finance Statistics Manual (GFSM) 2014 to distinguish grants, subsidies, and other expenses; (ii) review of the new chart of accounts (CoA) and mapping from the old chart to the new one; (iii) compilation of government expenditure using the classification of functions of government (COFOG); and reviewed progress on the migration plan to GFSM 2014 compliant compilation and reporting of fiscal and debt statistics. The mission was undertaken jointly with the IMF's Regional Technical Assistance Center in Southern Africa (AFRITAC South/AFS) Public Finance Management (PFM) TA mission.